Irrigation scheme research report - Sok, Sao; Klok, Sam Ang; Sithirith, Mak; De Silva, Sanjiv; Tuy, Sinak (WorldFish, 2024)
This research uses a working definition for FWUC adapted by MOWRAM (1999) as a government’s institution that brings together farmers for the purpose of managing a common irrigation system. Other definitions may apply to contexts of domestic water use or traditional irrigation groups. Here, we introduce the term “mainstream” FWUC to specify what is generally meant by the term FWUC in the frame of current government irrigation development projects. The main characteristics of mainstream FWUCs. FWUC is a user-based cooperative that aims to manage the irrigation system for its members mostly on a nonprofit basis, but it benefits to individual members. Its main tasks include the allocation of water within the irrigation system, operation and maintenance (O&M) of the system and the cost recovery of O&M through the collection of irrigation fees from its members. A FWUC is generally small in scale with a limited number of members (usually no more than several hundred members), so that self-management by users is possible. The actual size of a FWUC often depends on the irrigation system. For example, a FWUC may be responsible for one tertiary block that is subdivided into smaller units of Water User Groups (WUGs), or one FWUC may be responsible for the entire system.